Meeting Report: Translational Advances in Cancer Prevention Agent Development Meeting - Miller, Mark Steven (J Cancer Prev, 2021)
The Division of Cancer Prevention of the National Cancer Institute (NCI) and the Office of Disease Prevention of the National Institutes of Health co-sponsored the Translational Advances in Cancer Prevention Agent Development Meeting on August 27 to 28, 2020. The goals of this meeting were to foster the exchange of ideas and stimulate new collaborative interactions among leading cancer prevention researchers from basic and clinical research; highlight new and emerging trends in immunoprevention and chemoprevention as well as new information from clinical trials; and provide information to the extramural research community on the significant resources available from the NCI to promote prevention agent development and rapid translation to clinical trials. The meeting included two plenary talks and five sessions covering the range from pre-clinical studies with chemo/immunopreventive agents to ongoing cancer prevention clinical trials. In addition, two NCI informational sessions describing contract resources for the preclinical agent development and cooperative grants for the Cancer Prevention Clinical Trials Network were also presented.